2021
DOI: 10.3389/fdmed.2021.673626
|View full text |Cite|
|
Sign up to set email alerts
|

Periodontitis Is Associated With Risk of Conventional Stent Restenosis: Pilot Case-Control Study

Abstract: Objectives: Percutaneous coronary angioplasty with stent implantation has been established as the main form of treatment of atherosclerosis. However, 16 to 44% of patients may evolve with stent restenosis. Periodontitis is an inflammatory condition associated with bacterial infection, that may lead to periodontal tissue destruction and tooth loss. This study aimed to evaluate the association between stent restenosis and periodontitis.Materials and Methods: Coronary angiography exams presenting stent imaging wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The existing research has demonstrated that oral infection serves as an independent risk factor for the occurrence of ISR in patients with acute coronary syndrome (ACS) (OR = 1.202, 95% CI = 1.085–1.333, p < 0.01) [ 26 ]. Stages III and IV periodontitis are associated with an elevated incidence of ISR following coronary angioplasty (OR = 5.82) [ 27 ]. Furthermore, patients who experience ISR after percutaneous coronary intervention tend to have a higher severity of periodontal disease, among which 64.1% are classified as having Stage Ⅳ periodontitis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existing research has demonstrated that oral infection serves as an independent risk factor for the occurrence of ISR in patients with acute coronary syndrome (ACS) (OR = 1.202, 95% CI = 1.085–1.333, p < 0.01) [ 26 ]. Stages III and IV periodontitis are associated with an elevated incidence of ISR following coronary angioplasty (OR = 5.82) [ 27 ]. Furthermore, patients who experience ISR after percutaneous coronary intervention tend to have a higher severity of periodontal disease, among which 64.1% are classified as having Stage Ⅳ periodontitis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%